Emerging 2D Materials for Electrocatalytic Applications: Synthesis, Multifaceted Nanostructures, and Catalytic Center Design. Issue 17 (31st January 2022) - Wu, Xizheng; Xiao, Sutong; Long, Yanping; Ma, Tian; Shao, Wenjie; Cao, Sujiao; Xiang, Xi; Ma, Lang; Qiu, Li; Cheng, Chong; Zhao, Changsheng
Abstract: Currently, the development of advanced 2D nanomaterials has become an interdisciplinary subject with extensive studies due to their extraordinary physicochemical performances. Beyond graphene, the emerging 2D‐material‐derived electrocatalysts (2D‐ECs) have aroused great attention as one of the best candidates for heterogeneous electrocatalysis. The tunable physicochemical compositions and characteristics of 2D‐ECs enable rational structural engineering at the molecular/atomic levels to meet the requirements of different catalytic applications. Due to the lack of instructive and comprehensive reviews, here, the most recent advances in the nanostructure and catalytic center design and the corresponding structure–function relationships of emerging 2D‐ECs are systematically summarized. First, the synthetic pathways and state‐of‐the‐art strategies in the multifaceted structural engineering and catalytic center design of 2D‐ECs to promote their electrocatalytic activities, such as size and thickness, phase and strain engineering, heterojunctions, heteroatom doping, and defect engineering, are emphasized. Then, the representative applications of 2D‐ECs in electrocatalytic fields are depicted and summarized in detail. Finally, the current breakthroughs and primary challenges are highlighted and future directions to guide the perspectives for developing 2D‐ECs as highly efficient electrocatalytic nanoplatforms are clarified. This review provides a comprehensive understanding to engineer 2D‐ECs and may inspire many novel attempts and new catalytic applications across broad fields. Abstract : Recent nanostructure and catalytic center design of emerging 2D materials for electrocatalytic applications are summarized in this review. The synthetic pathways and state‐of‐the‐art strategies for designing these multifaceted 2D electrocatalysts are systematically discussed, especially promoting catalytic activities and exploring the corresponding structure–function relationships. Furthermore, the electrocatalytic applications, current challenges, and future directions in different fields are also summarized.